Design and implementation of a less invasive gastrostimulator - Laurent Lonys; Anne Vanhoestenberghe; Vincent Huberty; Martin Hiernaux; Nicolas Cauche; Nicolas Julémont; Adrien Debelle; François Huberland; Vicente Acuña; Carmen Godfraind; Jacques Devière; Alain Delchambre; et al. (PAGEPress Publications, 2016)
Gastrointestinal stimulator implants have recently shown positive results in helping obese patients lose weight. However, to place the implant, the patient currently needs to undergo an invasive surgical procedure. Our team is aiming for a less invasive procedure to stimulate the stomach with a gastrostimulator. Attempts covered fully endoscopic implantation and, more recently, we have focussed on a single incision laparoscopic procedure. Whatever the chosen implantation solution, the electronic design of the implant system shares many challenges. This paper covers the work achieved to meet these.